Sustaining Students’ Mental Health Through the Use of Tiktok Application - Alron Godrian E. Gajo; Edrel Mark P. Gaisen; Franz Von King R. Lino; Vivencio L. Calixtro Jr; Lilibeth B. Edaṅo (Indonesian Journal of Community and Special Needs Education, 2023)
The relationship between social media use and an increase in mental health problems has long been established. Since the TikTok application became the most widely used app in 2019 has been an issue with the students. This study was conducted primarily to assess students’ mental health through the use of the TikTok application. Quantitative data were collected from randomly selected college students within the Province of Sultan Kudarat who are using the TikTok application for almost a year regardless of gender with a total number of thirty (30), coming from different tertiary schools in Region XII.  Adapted test items in the survey questionnaire were made from Google forms and were disseminated online through messenger and Google mails, considering the Covid 19 pandemic. Descriptive analysis showed a positive impact between the level of engagement in terms of frequency of use, duration of use and the students’ use of TikTok application, the level of effects of the abovementioned application in students’ mental health; the level of students’ management of mental health in terms of academic stress, family crisis and peer pressure. Conclusion of these findings indicated that the use of TikTok application can raise awareness about the importance of using the said application with moderation and can help implement early interventions and prevention for the symptoms of any mental health issues associated with the identified common factors namely academic stress, family crisis, and peer pressure.